2020
DOI: 10.1177/0047239520943647
|View full text |Cite
|
Sign up to set email alerts
|

Flip It or Click It: Equivalent Learning of Vocabulary From Paper, Laptop, and Smartphone Flashcards

Abstract: Students frequently utilize digital devices and applications to assist studying. Past research has yielded mixed results on their effectiveness, and scant research has compared portable technologies with each other or focused on smartphones specifically. We compared college students’ learning of vocabulary on paper, laptop, and smartphone. Students were randomly assigned to one platform for reviewing vocabulary flashcards, and then they completed a memory quiz and answered questions regarding perceptions of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 54 publications
0
19
0
1
Order By: Relevance
“…It is quite correct to say that mobility was also available for the other two devices: smartphones and tablets. Still, laptops overcame those two devices in screen width, comfortableness, and mainly a device for information gathering (Sage, Piazzini, Downey, & Ewing, 2020). Compared to smartphones, several studies showed that laptops gave students more learning value and engagement other than not representing distractions or being detriments as smartphones (Albó, Hernández-Leo, & Oliver, 2019;Tossel, Kortum, Shepard, Rahmati, & Zhong, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…It is quite correct to say that mobility was also available for the other two devices: smartphones and tablets. Still, laptops overcame those two devices in screen width, comfortableness, and mainly a device for information gathering (Sage, Piazzini, Downey, & Ewing, 2020). Compared to smartphones, several studies showed that laptops gave students more learning value and engagement other than not representing distractions or being detriments as smartphones (Albó, Hernández-Leo, & Oliver, 2019;Tossel, Kortum, Shepard, Rahmati, & Zhong, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…With the move online, there was a quick need for students to use their personal devices to engage in coursework. As previously mentioned, smartphone ownership is near universal among the college student population (e.g., Sage et al, 2020 ). Laptop ownership is similarly high at above 90% (Gierdowski, 2019 ; Sage et al, 2020 ).…”
Section: Introductionmentioning
confidence: 94%
“…Faced with an indefinite timeframe and health measures such as quarantines, a shift to virtual learning was deemed a necessary measure to balance safety with education needs. Though the shift occurred quickly, ownership of mobile devices was already ubiquitous among the college student population (e.g., Gierdowski, 2019 ; Sage et al, 2020 ). Most students today own both smartphones and laptops, with smartphones often being the most popular as students find them convenient and helpful for communication (e.g., Anshari et al, 2017 ; Sage et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations